2013
DOI: 10.1177/0363546513496049
|View full text |Cite
|
Sign up to set email alerts
|

Healing Predictors of Stable Juvenile Osteochondritis Dissecans Knee Lesions After 6 and 12 Months of Nonoperative Treatment

Abstract: A 6-month period of nonoperative treatment with or without casting might be appropriate if the healing potential is >48%. A 12-month period of nonoperative treatment may be successful if the CLL is <1.3 mm in length as assessed on MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 40 publications
3
107
0
1
Order By: Relevance
“…In terms of natural history of the JOCD, Hughes et al [3] reported that most JOCD lesions with subchondral bone changes on the MRI had intact cartilage and improved with conservative treatment for 3-6 months. However, its failure rate has been reported and varies between 34 and 50% [4,5]. In our case, as shown in the MRI study at the time of the initial meniscectomy, the JOCD lesion with a high-intensity area in the T2-weighted images was diagnosed as a stable condition and left without any surgical intervention because of an absence of abnormal arthroscopic findings.…”
Section: Discussionmentioning
confidence: 50%
“…In terms of natural history of the JOCD, Hughes et al [3] reported that most JOCD lesions with subchondral bone changes on the MRI had intact cartilage and improved with conservative treatment for 3-6 months. However, its failure rate has been reported and varies between 34 and 50% [4,5]. In our case, as shown in the MRI study at the time of the initial meniscectomy, the JOCD lesion with a high-intensity area in the T2-weighted images was diagnosed as a stable condition and left without any surgical intervention because of an absence of abnormal arthroscopic findings.…”
Section: Discussionmentioning
confidence: 50%
“…Nonoperative treatment can fail in up to 50% of cases, and factors such as increasing patient age, the presence of cyst-like lesions, and lesion size contribute to the high failure rate. 2 If it fails, then successful healing can usually be achieved by arthroscopic fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Se procederá a reevaluaciones periódicas para evitar la atrofia muscular o el riesgo de rigidez articular residual. Entre el 50-67% de las OCD juveniles pueden curarse con tratamiento conservador en un periodo de 6 a 18 meses, aunque este porcentaje puede llegar al 90% en algunas series 9 .…”
Section: Acta Reumatológica Issn 2386-6861unclassified